Gut microbiota in obstructive sleep apnea–hypopnea syndrome: disease-related dysbiosis and metabolic comorbidities. (12th April 2019) - Ko, Chih-Yuan; Liu, Qing-Quan; Su, Huan-Zhang; Zhang, Hua-Ping; Fan, Ji-Mim; Yang, Jiao-Hong; Hu, An-Ke; Liu, Yu-Qi; Chou, Dylan; Zeng, Yi-Ming
Abstract : Gut microbiota alterations manifest as intermittent hypoxia and fragmented sleep, thereby mimicking obstructive sleep apnea–hypopnea syndrome (OSAHS). Here, we sought to perform the first direct survey of gut microbial dysbiosis over a range of apnea–hypopnea indices (AHI) among patients with OSAHS. We obtained fecal samples from 93 patients with OSAHS [5 < AHI ≤ 15 ( n =40), 15 < AHI ≤ 30 ( n =23), and AHI ≥ 30 ( n =30)] and 20 controls (AHI ≤ 5) and determined the microbiome composition via 16S rRNA pyrosequencing and bioinformatics analysis of variable regions 3–4. We measured fasting levels of homocysteine (HCY), interleukin-6 (IL-6), and tumor necrosis factor α (TNF-α). Results revealed gut microbial dysbiosis in several patients with varying severities of OSAHS, reliably separating them from controls with a receiver operating characteristic-area under the curve (ROC-AUC) of 0.789. Functional analysis in the microbiomes of patients revealed alterations; additionally, decreased in short-chain fatty acid (SCFA)-producing bacteria and increased pathogens, accompanied by elevated levels of IL-6. Lactobacillus levels correlated with HCY levels. Stratification analysis revealed that the Ruminococcus enterotype posed the highest risk for patients with OSAHS. Our results show that the presence of an altered microbiome is associated with HCY among OSAHS patients. These changes in the levels of SCFA affect the levels of pathogens that play a pathophysiological role in OSAHS and related metabolic comorbidities.